Komplementarität als Königsweg christlicher Friedensethik?: Kontroversen im Spannungsfeld von Pazifismus und militärischer Gewalt - Werkner, Ines-Jacqueline (Sicherheit und Frieden, 2013)
The issue of the use of military force has been and remains the subject of controversial debate in Christian thinking. The fact of German rearmament brought forward two main Christian schools of thought which were irreconcilably opposed: on the one hand, those who, due to the still unredeemed world, deem it necessary to resort to military means in order to ensure peace if need be; and on the other hand, those who, in view of the message of the gospel, rejected all use of military force in the here and now. As an attempt to solve this conflict, it was suggested to refer to both positions as “complementary”. Now, the debate is dominated by the question of responsibility to protect, combined with the issue of the legitimacy of the use of military force to protect groups of the population who are in danger. On this basis, the question arises to what extent complementarity can still be considered as a “silver bullet” of the peace ethics positioning. (S+F/Pll)
Keywords: Deutschland -- Bundesregierung; Evangelische Kirche in Deutschland